2018
DOI: 10.1038/s41598-018-29033-1
|View full text |Cite
|
Sign up to set email alerts
|

Precoce and opposite response of proteasome activity after acute or chronic exposure of C. elegans to γ-radiation

Abstract: Species are chronically exposed to ionizing radiation, a natural phenomenon which can be enhanced by human activities. The induced toxicity mechanisms still remain unclear and seem depending on the mode of exposure, i.e. acute and chronic. To better understand these phenomena, studies need to be conducted both at the subcellular and individual levels. Proteins, functional molecules in organisms, are the targets of oxidative damage (especially via their carbonylation (PC)) and are likely to be relevant biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…After chronic irradiation, a recent study of our team has shown that reproduction is the more sensitive macroscopic parameter regarding survival and growth [17]. Moreover, our first study has also highlighted that, contrary to acute irradiation, chronic irradiation from 3.3 Gy induced a decrease of the number of progeny without impacting the hatching success [4]. This could suggest that in such conditions, gametogenesis is more impacted than embryogenesis.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…After chronic irradiation, a recent study of our team has shown that reproduction is the more sensitive macroscopic parameter regarding survival and growth [17]. Moreover, our first study has also highlighted that, contrary to acute irradiation, chronic irradiation from 3.3 Gy induced a decrease of the number of progeny without impacting the hatching success [4]. This could suggest that in such conditions, gametogenesis is more impacted than embryogenesis.…”
Section: Introductionmentioning
confidence: 66%
“…Indeed our first results showed that a decrease of the number of progeny associated with a decrease of the embryo hatchability occurred from and above 30 Gy of acute irradiation [4]. In this paper, the decrease of the progeny number per individual have been hypothesized to be correlated to an increase of apoptosis whereas an explanation for the decrease of hatching success can be unrepaired DNA-damage then leading to non-viable eggs.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations